2008
DOI: 10.1210/en.2007-1192
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor (TNF)-α Persistently Activates Nuclear Factor-κB Signaling through the Type 2 TNF Receptor in Chromaffin Cells: Implications for Long-Term Regulation of Neuropeptide Gene Expression in Inflammation

Abstract: Chromaffin cells of the adrenal medulla elaborate and secrete catecholamines and neuropeptides for hormonal and paracrine signaling in stress and during inflammation. We have recently documented the action of the cytokine TNF-alpha on neuropeptide secretion and biosynthesis in isolated bovine chromaffin cells. Here, we demonstrate that the type 2 TNF-alpha receptor (TNF-R2) mediates TNF-alpha signaling in chromaffin cells via activation of nuclear factor (NF)-kappaB. Microarray and suppression subtractive hybr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 56 publications
2
33
0
Order By: Relevance
“…This contrasts with the JNK and p38 pathways normally associated with TNF-a actions in lymphoid cells. In a subsequent study, the same group showed that TNF-a activation of bovine adrenal chromaffin cells resulted in a persistent activation of the NFjB pathway (Ait-Ali et al 2008). Microarray and suppression subtractive hybridization identified a number of TNF-a target genes including not only the expected neuropeptides (VIP and galanin) but also the long-term activation of a number of NFjB-associated genes including IjB and mitogen-inducible gene-6.…”
Section: Tumour Necrosis Factor-amentioning
confidence: 94%
See 1 more Smart Citation
“…This contrasts with the JNK and p38 pathways normally associated with TNF-a actions in lymphoid cells. In a subsequent study, the same group showed that TNF-a activation of bovine adrenal chromaffin cells resulted in a persistent activation of the NFjB pathway (Ait-Ali et al 2008). Microarray and suppression subtractive hybridization identified a number of TNF-a target genes including not only the expected neuropeptides (VIP and galanin) but also the long-term activation of a number of NFjB-associated genes including IjB and mitogen-inducible gene-6.…”
Section: Tumour Necrosis Factor-amentioning
confidence: 94%
“…As with IL-1a/b, TNF-a induces neuropeptide expression and secretion from isolated bovine chromaffin cells; indeed, it was notably more potent than the former cytokine (Turquier et al 2002;Ait-Ali et al 2008;Ait-Ali et al 2004). This was particularly marked in the case of the neuropeptide galanin where a 72-h incubation with TNF-a induced an almost 100-fold increase in its mRNA levels compared to only 2-fold in response to IL-1a/b (Ait- Ali et al 2004).…”
Section: Tumour Necrosis Factor-amentioning
confidence: 94%
“…Although TNFR1, through boosting NF-B activation, was found to response to broad inflammation stimulation in various diseases (1), TNFR2 was considered to function preferably on several special kidney diseases (2)(3)(4). Recently TNFR2 was reported to be activated by TNF-␣ and to further activate NF-B in certain types of cells (5)(6)(7). It appears that TNFR2 induces activation of NF-B signaling differentially under a specific inflammatory condition with an assistance of some co-factors.…”
Section: Tnf-␣ Exerts Its Biological Effects Via Two Functionally Dismentioning
confidence: 99%
“…Isolated ACCs were plated on 16-mm glass coverslips coated with poly-D-lysine (2 mg/ml) and laminin (20 g/ml). Cells were cultured overnight at 37°C and 5% CO 2 ]i) was monitored in isolated ACCs using ratiometric analysis of the fluorescent Ca 2ϩ indicator dye fura 2-AM. ACCs were incubated in DMEM containing 2.5 M fura 2-AM (dissolved in DMSO; Invitrogen) for 30 min at 37°C to allow for uptake of the dye.…”
Section: Animals and Materialsmentioning
confidence: 99%
“…ACCs are located within the adrenal medullae, highly vascularized structures that contain fenestrated capillaries (53) that are permeable to large molecules, such as cytokines. ACCs express receptors for cytokines that are systemically elevated during IBD, including tumor necrosis factor (TNF)-␣ and interleukin (IL)-6 (1,2,26,36,43). Furthermore, inflammatory mediators have been shown to alter I Ca and catecholamine secretion in ACCs in vitro (48,60).…”
mentioning
confidence: 99%